Dental anxiety among Bangladeshi patients: a cross-sectional study (Bioresearch Communications, 2025)
Background: A significant portion of patients are suffering from dental anxiety all around the world. Dental anxiety is often a barrier for many patients for not taking treatment. It causes a huge discomfort in patients, often results in missing, delaying or cancelling dental appointments, and so impacts on the overall quality of life of a person. Objective: The main objective of this study was to assess the prevalence of dental anxiety and associated factors among dental patients in Bangladesh. Methods: This cross-sectional study utilized the validated Bangla Modified Dental Anxiety Scale (BMDAS). The BMDAS consists of five questions to assess dental anxiety. Data were collected from government settings hospitals. Results: Data were collected from 311 dental patients. It was found that 23.5% of the patients were experiencing dental anxiety. Predictors of dental anxiety among study participants were age, educational qualification, and past dental visits. Younger patients (M = 14.38, SD = 5.62) have been found to have more dental anxiety (p